Pengaruh Risk Aversion Terhadap Keputusan Investasi pada Generasi Milenial di Karawang - Karolin, Simbolo, Paulina; Situngkir, Tiar Lina; Kusumawardaya, Vandita (Value : Journal of Management and Business, 2024)
This research uses a survey research design to see how risk aversion influences investment decisions made by the millennial generation in Karawang. Risk aversion is the independent variable, and investment decisions are the dependent variable. This study focuses on the millennial generation population in Karawang, which numbers around 1,029,290 people. In addition, 429 respondents from the millennial generation who were actively involved in investment activities were the sample used in this research. In this research, the influence of risk aversion on investment decisions is tested through Simple Linear Regression Analysis. Studies show that fear of risk influences millennials' investment choices. This generation prefers to avoid danger. They prefer to invest in instruments that they consider more stable and easy to understand. The results show that to help millennials make smarter and more logical investment choices, increased financial education is needed.